Horizontal seismic force demands on nonstructural components in low-rise steel building frames with tension-only braces. (1st August 2018) - Hou, Hetao; Fu, Weiqi; Wang, Wei; Qu, Bing; Chen, Yiyi; Chen, Yueshi; Qiu, Canxing
Highlights: The system can be promptly recovered after a major earthquake. The repaired systems behave as the original ones. The dynamic amplification factor is period-dependent. Distributions of peak floor accelerations are excitation-intensity-dependent. The use of stiff exterior walls can increase demands on nonstructural components. Abstract: Steel building frames consisting of tension-only braces have been recently recognized as adequate lateral force resisting systems for use in low-rise buildings in the regions with seismicity. To further promote the use of such systems, this investigation was focused on developing recommendations for calculating the horizontal seismic force demands on the nonstructural components attached to the systems. Specifically, two full-scale three-story experimental models were designed, constructed and tested using shake tables. The two experimental models differed from each other primarily in that one model consisted of the exterior walls with non-negligible contributions to the system lateral stiffness while the other experimental model did not have such exterior walls. A series of shake table tests using the excitations scaled to different intensity levels were performed on each experimental model. It was found that the existing design and analysis methods appear inadequate in predicting the horizontal seismic force demands on the nonstructural components. Based on the test results, a practical model which can well capture the central tendency of the test results and can be integrated into the existing design method was developed. Test results also revealed that the exterior walls with non-negligible contributions to the system lateral stiffness can arouse larger horizontal seismic force demands on the nonstructural components.